Kapabilitas Humas Perguruan Tinggi Di Jakarta Dalam Tata Kelola Komunikasi MBKM Saat Pandemi COVID-19 - Harwinda, Alfilonia; Pinariya, Janette Maria; Putri, Dhita Widya; Yunia, Anita; Yulianti, Wulan (LUGAS Jurnal Komunikasi, 2024)
During the COVID-19 pandemic, public relations in Higher Education (PT) is facing new changes.  The public relations capability is  to maintain  relations with the media, internal and external communications  other  stakeholders.  This  is related to the PT's public relations capabilities in information management during COVID-19, which can provide clear and  good  information and maintain the reputation and image of the organization. This research aims to understand the Public Relations Capabilities in (PT) for information management during the COVID-19 pandemic.  This research  to  used by Macnamara (2018) regarding Knowledge, Skills, and Abilities (KSAs)/ Competencies, Competency, and Competence.  This research uses qualitative methods and data collection using Focus Group Discussions (FGD) with 13 public relations employees from universities in Jakarta.  PT's public relations capability in managing information to the internal and external via social media channels effectively regarding MBKM.   Public relations officer can carry out a competency test  which  is  useful for  becoming a reliable and competent public relations officer and understanding the basics of the PR code of ethics. Public relations in (PT) capabilities during the COVID-19 pandemic by having public relations competencies that have a role in professional performance ethics. Evaluation and monitoring have successfully navigated academic activities during the pandemic and ready to face the new normal. The role of public relations in (PT) is related to the Good Reputation of the organization and its stakeholders. Public relations in (PT) to attract the  attention of the audience  (lecturers and students) by creating  interesting  content about MBKM uploaded via social media and collaborating with other campus partners. Public relations in (PT) has implemented strich health protocols and established pandemic response task forces.